AN EXISTENCE RESULT FOR SYSTEMS THAT APPEAR IN - Dragoş-Pătru COVEI (Fiabilitate şi Durabilitate)
Many of the engineering developments often occur as a result of the intersection betweenscientific communities with system of differential equations. They, although discussed in manypapers from the specialized literature, still are not completely solved. The state of fact is expectedbecause practical applications reveal complexity and aspects that allow new approaches. From thispoint of view and from these reasons such problems shall continue to be characteristic feature ofactivities and tasks taken by scientific research, of major significance in mathematics. Related to thecontext and with a rough processing of the information taken from many bibliographic titles, thisarticle develops or generalizes certain previous results regarding systems of the Schrödinger type